Large linear-in-temperature resistivity in twisted bilayer graphene - Polshyn, Hryhoriy; Yankowitz, Matthew; Chen, Shaowen; Zhang, Yuxuan; Watanabe, K.; Taniguchi, T.; Dean, Cory R.; Young, Andrea F. (Nature physics, 2019)
Twisted bilayer graphene has recently emerged as a platform for hosting correlated phenomena. For twist angles near θ ≈ 1.1°, the low-energy electronic structure of twisted bilayer graphene features isolated bands with a flat dispersion 1 , 2 . Recent experiments have observed a variety of low-temperature phases that appear to be driven by electron interactions, including insulating states, superconductivity and magnetism 3 – 6 . Here we report electrical transport measurements up to room temperature for twist angles varying between 0.75° and 2°. We find that the resistivity, ρ , scales linearly with temperature, T , over a wide range of T before falling again owing to interband activation. The T -linear response is much larger than observed in monolayer graphene for all measured devices, and in particular increases by more than three orders of magnitude in the range where the flat band exists. Our results point to the dominant role of electron–phonon scattering in twisted bilayer graphene, with possible implications for the origin of the observed superconductivity. Transport measurements on twisted bilayer graphene show that a large linear-in-temperature increase in resistivity exists for many twist angles. This may have implications for the mechanism of superconductivity in this material.